SULIT AIR SEPAKAT DI KOTA SUNGAI PENUH: STUDI SEJARAH KELEMBAGAAN 1970-2022 - Primadona Primadona; Hendra Naldi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research is a study of the history of institutions that discusses the Agreeable Water Difficult Organization (SAS) in Sungai Full City in 1970-2022. The aim of the research was to find out the background and development of the Agreeable Water Difficult Organization in Sungai Full City in 1970-2022. This study uses the historical method which consists of four steps, namely heuristics (source gathering), verification (source criticism), interpretation (interpretation) and historiography (writing). The results of this study are that SAS Sungaipuh is a social organization of Minangkabau migrants which was founded in 1970. The background to the founding of SAS SungaiFull was caused by the large number of water-deficient immigrants who were in SungaiFull. The development of SAS in SungaiFull is inseparable from the role of the Difficult Air migrants who continue to establish friendly relations and good cooperation among fellow members of the organization. However, due to various factors, there are not so many members who are active in management and also the interest of members is decreasing over time.